OPTIMASI TEKNIK WESTERN BLOT UNTUK DETEKSI EKSPRESI PROTEIN TANAMAN PADI (Oryza sativa L.) - Susianti, .; Sukmana, Edi; Lesmana, Ronny; Supratman, Unang (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
Optimization of Western Blot Technique for Protein Expression of Rice Plant (Oryza sativa L.)Â Western blot (WB) technique has been widely used for analyzing protein expression and for identifying specific proteins derived from animals, plants, and microorganisms. During the use of WB, especially in agricultural studies, some difficulties are encountered such as unclear or unspecific protein bands, the presence of bubbles, and the absence of protein bands on membrane. This study aims to determine the WB conditions appropriate for the protein expression of rice plants (Oryza sativa L.). Protein from rice plant was extracted and the obtained protein lysate was then used for proteomic analysis using western blot with Î²-actin antibody. Our experiment showed that some optimized parameters like blocking buffers, the concentration of primary antibody and the ratio of secondary antibody determined the clarity of the results. Î²-actin was used as internal control that measured the success of the WB technique. Results showed that lysis process was important in determining good WB results in addition to the optimal blocking solution using a BSA of 0.2%, a primary antibody concentration of 1 Î¼g mLâ€“1, and a secondary antibody of 1:10,000. Optimizing techniques during extraction, incubation, and documentation facilitated good WB results.Keywords: Î²-actin; optimization; protein; rice plant; western blotABSTRAKTeknik western blot (WB) telah banyak digunakan untuk analisis ekspresi protein dan mengidentifikasi protein spesifik dari hewan, tumbuhan dan mikroorganisme. Dalam implementasi teknik WB, khususnya studi dalam bidang pertanian, beberapa kesulitan ditemui seperti pita protein tidak jelas, tidak spesifik, adanya gelembung, hingga tidak munculnya pita protein pada membran. Penelitian ini bertujuan untuk mengetahui kondisi WB yang tepat untuk deteksi protein tanaman padi (Oryza sativa L.). Protein tanaman padi diekstraksi, kemudian lysate protein yang didapat dianalisis dengan metode westernblot menggunakan antibody Î²-actin. Penelitian kami menunjukkan bahwa beberapa parameter yang dioptimasi seperti larutan blocking, konsentrasi antibodi primer dan rasio antibodi sekunder akan menentukan hasil yang jelas. Î²-actin digunakan sebagai kontrol internal yang menjadi tolok ukur keberhasilan teknik WB. Hasil menunjukkan bahwa proses lisis menjadi hal penting dalam menentukan hasil WB yang baik disamping larutan blocking yang optimal menggunakan BSA 0,2%, konsentrasi antibodi primer 1 Âµg mLâ€“1 dan antibodi sekunder 1:10.000. Mengoptimalkan teknik selama ekstraksi, inkubasi dan dokumentasi membantu mendapatkan hasil WB yang baik.